Why I hate flying - Mintzberg, Henry (Texere, 2001)
As all travelers know, flying is no simple matter. There are the horrors of the check-in to be negotiated, the uneven struggle to squash your hand luggage into the overhead locker and the constant fight with your neighbor over ownership of the armrest. Add to that the question of the food, the immigration queues and waiting for your luggage to appear and we can all see that something isnÂ't quite right. So when one of the worldÂ's leading management gurus Â- Henry Mintzberg Â- decides to scrutinize the managment practices of the airlines and airports from his personal experience, it is worth taking notice. And when he does it in a highly amusing manner; it is worth reading